Pengaruh Kedisiplinan Dan Kemandirian Belajar Terhadap Hasil Belajar Siswa Kelas XI Akuntansi Di SMK Harapan Mekar 2 Medan Tahun Ajaran 2021/2022 - Nurlaili, Siti; Novianti Sitompul, Dian (Jurnal Riset Ilmu Pendidikan, 2022)
This study aims to determine the effect of discipline and independent learning on the learning outcomes of students in class XI Accounting at SMK Harapan Mekar 2 Medan. The sample population in this study were students of class XI Accounting, amounting to 37 people, while the data collection technique used a questionnaire (questionnaire). Data analysis techniques collect prerequisite tests (normality test, linearity test and multiple linear regression analysis) and hypothesis testing (partial test (t-test), simultaneous test (F-test), and coefficient of determination).  Based on the results of data analysis using the SPSS 16.0 program, the research hypothesis using multiple linear regression testing was Y= 7,365 + 0,082 X1 + 0,472 X2. This means that if the constant value is 7.365, which means that if the variables X1 and X2 are equal to zero, then Y is 7.365. X1 regression coefficient value of 0.082 indicates if X1 has increased by 100% it will increase learning outcomes by 8.2%. X2 regression coefficient value of 0.472 indicates if X2 has increased by 100% it will increase learning outcomes by 47.2%. The results of the hypothesis test using the t-test of learning discipline obtained the value of tcount > t table, which is 2.141 > 2.026 with a probability of Sig 0.040 < 0.05. The results of the hypothesis test of the t-test of learning independence obtained that the value of tcount > ttable was 5.569 > 2.026 with a probability of Sig 0.000 <0.05. The results of the simultaneous test (F test) obtained a significant value of 0.000 <0.05. If we compare the value of Fcount with Ftable, the result is 23,310 > 3,250. The results of the coefficient of determination (R2) have an Rsquare value of 0.578 or equal to 57.8%, meaning that learning discipline and learning independence are able to explain the learning outcomes of Class XI Accounting Students at SMK Harapan Mekar 2 Medan amounting to 57.8% and the remaining 42, 2% is explained by other independent variables that are not included in this research model. This means that there is an influence between learning discipline and learning independence on the learning outcomes of students at SMK Harapan Mekar 2 Medan T.P 2021/2022.